Advancing water security in semi-arid Brazil: expansion of water storage infrastructure and human-water system co-evolution - Pereira, Bruno; Medeiros, Pedro; Meira Neto, Antônio Alves; de Araújo, José Carlos; Sivapalan, Murugesu (Frontiers in Water, 2025)
The study focuses on the history of expansion of water infrastructure and drought mitigation measures, through construction of a large network of reservoirs over a 100-year period in the Jaguaribe River Basin, in the state of Ceará, Brazil. The goal is to assess why and how a dense network of reservoirs came to be constructed, and the influence of natural and socio-economic factors, using the findings to develop a conceptual understanding of how the search for water security might have unfolded in this Brazilian semi-arid region. We analyze historical data on the change in the region’s hydrologic variability and the socio-economic drivers of agricultural development, supported by quantitative measures of water security generated through the application of a hydrologic model that accounts for the effect of reservoirs on hydrologic variability. Based on the historical analysis and model outputs, the history of the search for water security is organized into four distinct eras, recognizing changes in human aspiration that contributed to the transition between the eras. Water security during Era 1 is limited by water Availability; during Era 2 the limiting factor turned to Accessibility; during Era 3 it turned to Acceptability; and finally, during Era 4, the current period, the limiting factor for water security is water Quality. The temporal dynamics associated with the pursuit of water security can thus be seen as the emergent outcome resulting from two-way feedback embedded in a coupled human-water system. The organization into the four distinct eras happens to align neatly into the United Nations AAAQ (Availability, Accessibility, Acceptability and Quality) framework, which identifies potential barriers to services in humanitarian contexts. The conceptual understanding gained from the analysis of the expansion of water storage infrastructure experienced in the Brazilian semi-arid places the pursuit of water security more broadly within the ambit of coupled human-water systems research, and also provides empirical evidence for the applicability of the AAAQ framework in synthesizing knowledge drawn from multiple places. In this way the study contributes to the understanding of the drivers and feedbacks in human-water system dynamics over long temporal timescales, which is the ultimate ambition of socio-hydrology as a scientific discipline.